The interdependencies of stock market based on Small Capital Index in Southeast Asia: Singapore, Thailand, Indonesia and Vietnam to Malaysian Stock Market / Rushaniza Ruslan - Ruslan, Rushaniza (2015)
The purpose of this study is to identify the interdependencies between Singapore Stock Exchange small capital index, Stock Exchange of Thailand small capital index, Indonesia Stock Exchange small capital index and Vietnam Stock Exchange (Ho Chi Minh Stock Exchange and Hanoi Stock Exchange) small capital index to the FTSE Bursa Malaysia KLCI Index. The method has been used to find the interdependencies among those markets were Single Linear Regression and Multiple Linear Regression. Daily closing price of stock indices is collected from 1st January 2005 until 31st December 2014. According the result based on Single Linear Regression, it reveals that all independent variables: Singapore Stock Exchange, Stock Exchange of Thailand, Indonesia Stock Exchange and Vietnam Stock Exchange (Ho Chi Minh Stock Exchange and Hanoi Stock Exchange) have significant relationship towards FTSE Bursa Malaysia KLCI Small Capital Index. In the other hand, from the result of Multiple Linear Regression, it reveals that all these stock indices have a significant positive relationship towards FTSE Bursa Malaysia KLCI Small Capital Index. It means that there are interdependencies among this Southeast Asia stock market in term of small capital index. These results further our understanding of the relationship between the stock market in Southeast Asia and should be useful for regulator, investor and speculator.